If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7/2-2x=-1/2
We simplify the equation to the form, which is simple to understand
-7/2-2x=-1/2
Simplifying:
-3.5-2x=-1/2
Simplifying:
-3.5-2x=-0.5
We move all terms containing x to the left and all other terms to the right.
-2x=-0.5+3.5
We simplify left and right side of the equation.
-2x=+3
We divide both sides of the equation by -2 to get x.
x=-1.5
| ((4x^2)-2x+6)/(2x-3) | | 65-7x=2x+23 | | -5(k+3)+4k=3(k-5) | | 80=5*2b | | -2-(6)= | | 25x+30y=120 | | .1(.1x+.9)= | | 3y=3y+18 | | -6(x-2)=12-3x | | 15+6x=25+5x | | 5x-2(-x-6)=-37 | | x^2=4x-6 | | 3+8q=5+7q | | 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= | | E=5r+18 | | -4.75+2.19= | | +13-(+18)= | | 5.5=2+d | | 6(L+2)=36-6L | | 10-3x=-3(x-4) | | 13-18= |